Angioplasty of Dysfunctional Dialysis Fistula or Graft with Resveratrol-Excipient and Paclitaxel-Coated Balloon Improves Primary Patency Rates Compared to Plain Angioplasty Alone - Novak, Matej; Matras, Patrik; Kavan, Jan; Lambert, Lukas; Burgetova, Andrea (Journal of clinical medicine, 2022)
In this prospective randomized single-blinded study (reg. ISRCTN11414306), 76 patients with a dysfunctional dialysis fistula or graft due to a single de novo or recurrent stenosis in the access circuit were randomized to receive either conventional PTA (POBA) as a standard of care (n = 38) or PTA + adjunctive PTA with a drug-coated (paclitaxel-resveratrol matrix) SeQuent® Please OTW balloon (n = 38, DCB). Patients were scheduled for follow-up PTA at 3, 6, 9, and 12 months. The time of clinically driven target-lesion reintervention rate (primary patency rate) after the index procedure was analyzed using the log-rank test. The primary patency rates at 12 months after the index procedure were 17% (DCB) vs. 11% (POBA). At 3 months, they were 87% vs. 74%, at 6 months they were 53% vs. 26%, and at 9 months they were 22% vs. 11%. The hazard ratio for DCB was 0.55 (95%CI 0.32 to 0.95). The median time needed for target-lesion reintervention was longer in the DCB group (181 days) than in the conventional PTA group (98 days, p = 0.019). We conclude that PTA with the paclitaxel-resveratrol drug-coated SeQuent® Please OTW balloon in patients with de novo or recurrent stenosis in dialysis arteriovenous fistulas or grafts prolongs the time needed for target lesion reintervention and improves primary patency rates in the first year after the index procedure.
Keywords: drug-coated balloon; stenosis; hemodialysis; vascular access; angioplasty; resveratrol; paclitaxel